Sistem Aguron-guron di Griya Agung Bangkasa Kecamatan Abiansemal Kabupaten Badung - Ambarnuari, Mery; Gaduh, Acyutananda Wayan; Sandhi, Komang Diandika Darma Wiraga (Kamaya: Jurnal Ilmu Agama, 2024)
The aguron-guron system is an educational system developed by the Hindu religion to teach knowledge and skills in the religious field. The system is still highly relevant for imparting spiritual knowledge in the process of producing a pandita/sulinggih (spiritual teacher). The pandita, as a spiritual leader, holds a significant position and authority in the religious life of the Hindu community. Research related to the aguron-guron system was conducted at Griya Agung Bangkasa because this griya (household) is one of the ancient griyas with a long lineage of sulinggih and is committed to developing the aguron-guron system. There are three issues addressed in this research, namely related to the form, function, and implications of the aguron-guron system in Griya Agung Bangkasa. This qualitative research with a theological approach uses structural functionalism and symbolic interactionism theories to analyze the issues so that data can be presented descriptively qualitatively. The form of the aguron-guron system in Griya Agung Bangkasa is an education system known as "Garis Kapurusan Parampara." This education system is implemented intensively and exclusively by teachers/nabe towards their students/sisya. The aguron-guron education is carried out with the aim of achieving parartha and paramartha. The components involved include nabe, nanak, curriculum, walaka griya, and overseeing foundations. The aguron-guron system in Griya Agung Bangkasa serves educational, religious, and social functions. Lastly, regarding the implications of the aguron-guron system in Griya Agung Bangkasa, it gives rise to educational, theological, and sociological implications both internally and externally. This exclusive aguron-guron system is unique due to the presence of pawintenan wiwa and the existence of nabe siksa in the process, both of which are efforts to improve the quality of the implemented aguron-guron education. The exclusive nature of the aguron-guron system is the best choice for providing spiritual education, enriching the educational system, and creating a holistic education.